2021
DOI: 10.1038/s41564-021-00940-w
|View full text |Cite
|
Sign up to set email alerts
|

A heat-shock response regulated by the PfAP2-HS transcription factor protects human malaria parasites from febrile temperatures

Abstract: Periodic fever is a characteristic clinical feature of human malaria, but how parasites survive febrile episodes is not known. Although Plasmodium spp. genomes encode a full set of chaperones, they lack the conserved eukaryotic transcription factor HSF1, which activates the expression of chaperones upon heat-shock. Here, we show that PfAP2-HS, a transcription factor in the ApiAP2 family, regulates the protective heat-shock response in Plasmodium falciparum . PfAP2-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 70 publications
0
54
0
Order By: Relevance
“…This study identified some functional RNA structural elements, demonstrated that a dynamic RNA structurome responds to two different temperatures, and identified novel RNA thermometers. Our study adds to the accumulating evidence that febrile temperatures can suppress the growth and development of parasites with a maximal effect on trophozoites ( Tinto-Font et al, 2021 ). We identified a global trend of significantly reduced average icSHAPE scores for entire transcripts at 26°C compared with those at 37°C in the trophozoite stage based on the icSHAPE in vivo , as well as icSHAPE in vitro .…”
Section: Discussionmentioning
confidence: 53%
“…This study identified some functional RNA structural elements, demonstrated that a dynamic RNA structurome responds to two different temperatures, and identified novel RNA thermometers. Our study adds to the accumulating evidence that febrile temperatures can suppress the growth and development of parasites with a maximal effect on trophozoites ( Tinto-Font et al, 2021 ). We identified a global trend of significantly reduced average icSHAPE scores for entire transcripts at 26°C compared with those at 37°C in the trophozoite stage based on the icSHAPE in vivo , as well as icSHAPE in vitro .…”
Section: Discussionmentioning
confidence: 53%
“…The immediate stress response (cluster 2, Fig. 2e top panel) includes Hsp70-1, which has been previously shown to be transcriptionally induced in response to amino acid starvation (Pavlovic Djuranovic et al, 2020) and to be induced by the ApiAP2 transcription factor PfAP2-HS (PF3D7_1342900) after heat shock (Tintó-Font et al, 2021), suggesting it may be a central early stress response gene in the Plasmodium ISR downstream of various stimuli. Several other chaperones as well as the drug efflux pump MDR1 were also induced.…”
Section: Discussionmentioning
confidence: 99%
“…Over half of the ApiAP2 proteins are predicted to be essential for the IDC in P. falciparum (1517). In-depth studies of ApiAP2 proteins to date have demonstrated roles in transcriptional activation or repression affecting diverse processes including invasion(18, 19), heterochromatin maintenance(17, 2023), sexual and mosquito stage differentiation(16, 2434), and heat stress tolerance(35). Despite these properties which make ApiAP2 proteins potential drug targets, no efforts to date have focused on targeting the sequence specific DNA binding ApiAP2 transcription factors.…”
Section: Introductionmentioning
confidence: 99%